2015
DOI: 10.1016/j.forsciint.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chemical concentration and odor activity value explains the inconsistency in making a comprehensive surrogate scent training tool representative of illicit drugs

Abstract: This report highlights the importance of an individual chemical's odor impact in the olfactory identification of marijuana, cocaine, and heroin. There are small amounts of highly odorous compounds present in headspace of these drugs, with very low odor detection thresholds, that are more likely responsible for contributing to the overall odor of these drugs. Previous reports of the most abundant compounds in headspace can mislead researchers when dealing with whole odor of these drugs. Surrogate scent formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…It is defined as the ratio of peak area counts and odor detection threshold 49, 50 . The peak area count is used to quantify the amount of the compound’s presence in the total mixture.…”
Section: Resultsmentioning
confidence: 99%
“…It is defined as the ratio of peak area counts and odor detection threshold 49, 50 . The peak area count is used to quantify the amount of the compound’s presence in the total mixture.…”
Section: Resultsmentioning
confidence: 99%
“…All data and supporting documentation are publicly available via the Intermountain West Data Warehouse (IWDW) website (WAQS, 2017). The revision 2 of the Carbon Bond 6 (CB6r2) (Ruiz and Yarwood, 2013) chemistry mechanism was used in all model runs. This groups all monoterpenes as a single compound species, TERP.…”
Section: Emission Inventories For Cannabis Cultivation Facilities (Ccfs)mentioning
confidence: 99%
“…The contention that MB may not be the primary or sole signature odor of cocaine is supported by the studies of Rice and Koziel who reported that human odor detection thresholds for various VOCs associated with cocaine, heroin, and marijuana do not correlate with their headspace chemical concentrations. They propose that low concentrations of highly odorous compounds (i.e., very low odor detection thresholds) present in the headspace of these drugs may be primarily responsible for contributing to the overall odor of these drugs.…”
Section: Review and Analysis Of Scientific Literature On Canine Alertmentioning
confidence: 99%